Chemical Composition of Impatiens textori Miq. Flower Absolute and Its Potential Wound Repair and Anti-Melanogenesis-Promoting Activities in Skin Cells - Yu Rim Won; Kyung Jong Won; Do Yoon Kim; Mi Jung Kim; Bok Sil Hong; Hwan Myung Lee (MDPI AG, 2022)
Impatiens textori Miq. (ITM; family Balsaminaceae) is a traditional medicinal plant with many biological activities, which include anti-allergic, anti-inflammatory, and anti-pruritic properties. However, it remains to be determined whether ITM affects biological activities in the skin. Thus, we investigated the effects of ITM flower absolute (ITMFAb) extract on the biological activities of skin, especially those related to skin wound repair and whitening. ITMFAb was extracted with hexane, and its composition was determined through GC/MS. The biological activities of ITMFAb on HaCaT keratinocytes and B16BL6 melanoma cells were analyzed using a water-soluble tetrazolium salt, 5-bromo-2'-deoxyuridine incorporation, a Boyden chamber, an ELISA, a sprouting assay, and by immunoblotting. These analyses were performed in a range of ITMFAb concentrations that did not inhibit the viability of the cells (HaCaT, ≤400 µg/mL; B16BL6, ≤200 µg/m). Forty components were identified in ITMFAb. ITMFAb stimulated proliferation, migration, sprout outgrowth, and type I and IV collagen synthesis and upregulated the activations of ERK1/2, JNK, p38 MAPK, and AKT in HaCaT cells. In addition, ITMFAb attenuated the serum-induced proliferation of B16BL6 cells. ITMFAb inhibited melanin synthesis, tyrosinase activity, and expressions of MITF and tyrosinase in α-MSH-exposed B16BL6 cells. These findings indicate that ITMFAb has beneficial effects on wound repairing and whitening-linked responses in the skin and suggest the potential use of ITMFAb as a natural material for the development of skin wound repair and whitening agents.